Question
upstudy study bank question image url

Solve the compound inequality. \[ 3 x-2 \leq-5 \text { and } 4 x+3 \geq-17 \]

Ask by Schofield Jimenez. in the United States
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solution to the compound inequality is all x-values between -5 and -1, inclusive.

Solution

We are given the compound inequality:   3x - 2 ≤ -5  and  4x + 3 ≥ -17 Step 1. Solve the first inequality:   3x - 2 ≤ -5 Add 2 to both sides:   3x ≤ -3 Divide both sides by 3:   x ≤ -1 Step 2. Solve the second inequality:   4x + 3 ≥ -17 Subtract 3 from both sides:   4x ≥ -20 Divide both sides by 4:   x ≥ -5 Step 3. Combine the solutions: The first inequality gives x ≤ -1, and the second gives x ≥ -5. Together, x must satisfy both conditions:   -5 ≤ x ≤ -1 Thus, the solution to the compound inequality is all x-values in the interval [-5, -1].

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To solve the compound inequality \( 3x - 2 \leq -5 \) and \( 4x + 3 \geq -17 \), we will solve each inequality separately. 1. **Solve \( 3x - 2 \leq -5 \)**: - Add 2 to both sides: \[ 3x \leq -5 + 2 \] \[ 3x \leq -3 \] - Divide both sides by 3: \[ x \leq -1 \] 2. **Solve \( 4x + 3 \geq -17 \)**: - Subtract 3 from both sides: \[ 4x \geq -17 - 3 \] \[ 4x \geq -20 \] - Divide both sides by 4: \[ x \geq -5 \] Now we have the two inequalities: \[ x \leq -1 \] \[ x \geq -5 \] Putting these together, the solution to the compound inequality is: \[ -5 \leq x \leq -1 \] This can be expressed in interval notation as: \[ [-5, -1] \]

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy